1983
DOI: 10.1159/000176660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Zinc Supplements on Growth, Hormonal Levels, and Zinc in Healthy Short Children

Abstract: 13 short children aged 7–13 years who had a retarded bone age and low hair zinc concentration (under 140 µg/g) were treated with oral zinc supplements for a year. There was a significant increase in the growth rate in the children whose hair zinc concentration increased. Growth hormone, testosterone and somatomedin C also increased after oral zinc supplementation. Data from 755 short healthy children who have attended our Growth Clinic are presented which describe their hair and serum zinc concentration at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 17 publications
2
8
0
1
Order By: Relevance
“…Our findings were supported by other studies [3-5,17,18] who reported that Zn supplementation was effective for inducing growth in short children with Zn deficiency in a rate similar to that in healthy children. However, in some studies, this effect was not observed [6,7].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings were supported by other studies [3-5,17,18] who reported that Zn supplementation was effective for inducing growth in short children with Zn deficiency in a rate similar to that in healthy children. However, in some studies, this effect was not observed [6,7].…”
Section: Discussionsupporting
confidence: 91%
“…Low serum and hair zinc concentration and improved growth under oral zinc supple mentation were observed in most infants and children with growth retardation due to zinc deficiency [11,16,26,29,37], Therefore, it was of interest to compare parameters of zinc nutritional status of the infants enrolled in the three studies who were fed the formula without zinc fortification. Infants studied by Walravens et al [37] had substantially lower serum and hair zinc values at 6 months of age than infants studied by Higashi [19] at 5 months of age and the premature infants of this study at 121 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…Ghavami-Maibodi et al 9 acompanharam dois grupos de crianças com baixa velocidade de crescimento, suplementadas com doses variadas de zinco: um, com 50mg/Zn/dia por dois meses e, subseqüentemente, 50mg/Zn/dia uma vez por semana por dez meses; outro, com 100mg/Zn/ dia por um ano. Evidenciaram um aumento estatisticamente significativo tanto na taxa de crescimento, como nas concentrações de zinco no cabelo, soro e urina, de ambos os grupos, embora os efeitos fossem mais pronunciados no grupo suplementado com a dose maior.…”
Section: E F E I T O S D a S U P L E M E N T A ç ã O C O M Z I N C O unclassified